Assessment of Geologic Effect of Road Submergence Depths on Soil Subgrade Strength in Eket, South-South Nigeria (International Journal of Scientific Research and Management (IJSRM), 2022)
Road submergence is a common occurrence in Eket, South-South Nigeria, resulting in massive outlays for road construction and alimony. Fundamentally, the delineation of roadway structures is based on the strength of consolidated soil avowed as the subgrade. Consequently, the subgrade is the in situ material upon which the roadway structure is placed. It is necessary to know the modes of damage to roads caused by submergence. This study assesses the effect of road submergence depths and the extent of submergences on the subgrade strength of soil samples carried out on the Uquo Eket road that was intensely defective by the deluge. Coherent and frictional soil material types were tested for California Bearing ratio (CBR), mechanical analysis, Atterberg limit determination, and moisture density tests, respectively. CBR tests were done at various elevations of submersion, including common drenching limit, elongated deluge, and resoluteness of its suitability. Atterberg limit determination and mechanical analysis tests categorized and determined the applicability of studious soil as subgrade substantial. For elongated duration deluges, the depth and extent of submergence of subgrade strength show a lower value. Moreover, mechanical and Atterberg limit determination tests indicate a rapid and high-resolution occurrence of delegation for the elongated duration.